Professor psicólogo ou psicólogo professor? - Souza, Valdirene Brüning de (2016)
The regulation of psychology as a profession in Brazil occurred only in the 1960’s, and from it, the psychology teaching was also regulated, and the higher education for this professional was set as indispensable. Only years later psychologists graduated in the first psychology college courses have become university professors. However, they were not originally prepared to become university professors, as still occurs nowadays. Faced with this situation, the present research aimed to interpret how the professional identity construction of teachers of Higher Education of Psychology occurs. Thereunto, a case study was developed, with qualitative and exploratory characteristics, based on the phenomenological method. Thirteen teachers of a psychology college course in southern Brazil were interviewed, which represents 81.2% of the psychologists that are also teachers in this course. The results show that, although the teaching is seen as the main activity in the trajectory of the subjects, the professional identity of psychology professor develops itself partially in parallel to the psychologist identity. Professional identity is not something homogeneous, but hybrid between psychology and teaching. The professional patch, choices, trajectory, the as they build themselves as professionals is characterized by a come and go between teaching and psychology, searching for qualification, diverse experience, time dedication, but they do not define one by another, once they understand there is a complementarity. Professors searched highlighted the graduation courses in their teaching training; however, as they train researchers, these courses were not understood as fundamental on the contribution to pedagogical knowledge. Psychology professor learns to teach by teaching, like the other professionals who starts teaching in colleges nowadays, because the legal requirement in Brazil is the master and doctor’s degree. Out of the teaching field, the subject preferred activity is in the clinical psychology, for which direct most of the qualification efforts.